If it's not what You are looking for type in the equation solver your own equation and let us solve it.
d+3=-10-7/3d
We move all terms to the left:
d+3-(-10-7/3d)=0
Domain of the equation: 3d)!=0We add all the numbers together, and all the variables
d!=0/1
d!=0
d∈R
d-(-7/3d-10)+3=0
We get rid of parentheses
d+7/3d+10+3=0
We multiply all the terms by the denominator
d*3d+10*3d+3*3d+7=0
Wy multiply elements
3d^2+30d+9d+7=0
We add all the numbers together, and all the variables
3d^2+39d+7=0
a = 3; b = 39; c = +7;
Δ = b2-4ac
Δ = 392-4·3·7
Δ = 1437
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$d_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$d_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$d_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(39)-\sqrt{1437}}{2*3}=\frac{-39-\sqrt{1437}}{6} $$d_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(39)+\sqrt{1437}}{2*3}=\frac{-39+\sqrt{1437}}{6} $
| -7x+1=168 | | -23+2g=59 | | 0.6*8.847=1.1n | | 16n=7 | | 16.x+18.3=20.7 | | 5x+9(-1-7)=42 | | 2b-5=4(b+2) | | -6+11-4x=-5x-9 | | 0.6*8.47=1.1*n | | –6n8=n | | 8x-3(2x-4)=3(x | | −2(5x+6)+3(4x)=10 | | 147-x=272 | | √(3x-5)=12 | | 26-w=233 | | 6x=345 | | -9(x+3)+8=-19 | | X-8=x+10 | | 252=111-u | | x/4=6.2 | | t/10+50=57 | | X-8=-x-10 | | 200-30x=50 | | 206=124-u | | 5x/10=2x/12-10 | | 88=8(s+8) | | w/4+2=6 | | 7−8x=−9x+3 | | 0=(6x+7)(x-3) | | 8+11b=-(b+4) | | 177=98-y | | 2(h-8)-h-h=16 |